Provision of information by local governments using the Internet: case studies in Japan - Yoshio Arai (Netcom)
The Internet is an effective medium that has great potential for the low-cost provision of information from local government. This paper discusses the relationship between geographic conditions and local government policy for the use of Information and Communications Technologies (ICTs), via case studies of official websites operated by local governments in Japan. This paper explores three main issues. First, the process of the diffusion of local government websites in Japan is analyzed. Second, the diversity of website content presented by local governments is assessed. Finally, the effects of national policy on Internet utilization by local governments is discussed. The following results are based on data collected by a questionnaire survey and an analysis of websites for local governments in selected areas of Japan. The diffusion of official websites for local governments began in the mid-1990s and was largely complete by 2000. In the early stages of this diffusion process, many websites aimed to transmit information to audiences outside of the municipality. In the later stages, however, larger cities established official websites and a greater proportion of websites were internally oriented. The content of these sites targeted the multiple needs of the local residents in terms of public services. Although the Japanese Government established a positive policy with the aim of improving ICT utilization by both local and national government, the national policy had only a minor effect on official local government websites.